Performance analysis of an islanded variable speed wind energy system during multi-mode operation - Santhosam, P. Preethi; Sowmmiya, U; Sutikno, Tole (Institute of Advanced Engineering and Science, 2025)
Unbalances and non-linearities in islanded wind energy systems (WES) cause electromagnetic torque fluctuations, leading to mechanical stress and power oscillations. This study analyses the dynamic performance of a doubly fed induction generator (DFIG)-based variable speed WES connected to a standalone DC microgrid (DCM) during multimode operations. The proposed system addresses power balance during rare scenarios such as machine stall, closed rotor, and closed stator conditions. Notably, only one stator parameter regulates voltage and frequency, simplifying control and reducing cost. Unlike existing literature, this work quantifies and demonstrates the oscillations in torque, active, and reactive power. Dynamic performance is validated using a software-in-loop (SIL) approach with the Opal RT OP4510 real-time simulator. Results confirm that the system maintains voltage stability and supports uninterrupted power delivery across all operational modes. Additionally, power quality indices such as THD comply with IEEE 519 standards, reporting system reliability and flexibility in standalone wind energy applications.